2013
DOI: 10.7314/apjcp.2013.14.11.6233
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of Breastfeeding by Diabetic Women for Breast Cancer

Abstract: Diabetes represents a serious health problem. In the diabetic state, alterations in metabolism, increased susceptibility to infections and immunological changes occur. The suppression of the immune response has been identified as a relevant factor that contributes to the increase in the rate of infections in these patients. At the same time, breast cancer is the most frequent malignant tumor in women. The molecular and cellular mechanisms underlying cancer development have revealed that immune cells functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Clinical and epidemiological studies have shown that breastfeeding has a protective effect on breast cancer risk. 1 3 Accumulating evidence has suggested that human breast milk may confer long-term benefits, such as reduced risks of certain autoimmune diseases, inflammatory bowel disease, and certain malignancies. Some studies have also indicated that a reduced incidence of breast cancer is the most well-documented long-term effect of breastfeeding on mothers; 4 however, the degree to which some of these health benefits may be realized depends on the breastfeeding duration, breastfeeding frequency, breastfeeding exclusivity, and other personal factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and epidemiological studies have shown that breastfeeding has a protective effect on breast cancer risk. 1 3 Accumulating evidence has suggested that human breast milk may confer long-term benefits, such as reduced risks of certain autoimmune diseases, inflammatory bowel disease, and certain malignancies. Some studies have also indicated that a reduced incidence of breast cancer is the most well-documented long-term effect of breastfeeding on mothers; 4 however, the degree to which some of these health benefits may be realized depends on the breastfeeding duration, breastfeeding frequency, breastfeeding exclusivity, and other personal factors.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also indicated that a reduced incidence of breast cancer is the most well-documented long-term effect of breastfeeding on mothers; 4 however, the degree to which some of these health benefits may be realized depends on the breastfeeding duration, breastfeeding frequency, breastfeeding exclusivity, and other personal factors. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Immunological dysfunction, which is common in cancer patients and can be aggravated by surgery-induced traumatic inflammation, becomes one of the important risk factors for cancer (Franca et al, 2013;Yu et al, 2014). With the development of molecular biology, cytokine has received more and more attentions due to its critical role in traumatic inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental evidence has supported the hypothesis that colostrum is important in the protection against breast cancer [1] and can reduce the risk of disease in women who breastfeed [2,3]. Colostrum contains soluble and cellular components, such as lipids, carbohydrates, cytokynes, viable leukocytes [particularly macrophages] [4], and hormones, which are important for immune defense [5] and exhibit a circadian rhythm [6].…”
Section: Introductionmentioning
confidence: 99%